Sistem Informasi Manajemen Core Berbasis Mobile Pada Divisi FTM Telkom Akses Bandung - Bafadhal, Muzakkiy Abdul Latief; Suharto, Edi (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Mancore or also called core management is data management whose activities include recording data slots and fiber optic ports from the center to the ODC. The problem found at this time is that mancore data searches are carried out manually by ftm technicians in several telegram groups or in spreadsheets and are not stored in one database, so that incomplete mancore data is often found when technicians search in telegram groups. To overcome these problems, it is necessary to have a special application to store and search for mancore data. The new core management information system design uses a CRUD (Create, Read, Update, Delete) system, based on Android Mobile Application, and Firebase as its realtime database. Meanwhile, in making the design, it uses UML (Unified Modeling Language). With the creation of this core management information system application, it is hoped that it will make it easier for technicians to search for mancore data when making repairs, additions, and maintenance of fiber optic networks. because mancore data can be accessed in one application and mancore data can be accessed in real time in one database.